TINJAUAN FATWA MUI NOMOR: 1/MUNAS VII/MUI/5/2005 TENTANG HAK KEKAYAAN INTELEKTUAL (HaKI) TERHADAP PRAKTIK JUAL BELI BUKU FOTOKOPI DI SINTANG - Susirawati Susirawati; Syahbudi Syahbudi; Arif Wibowo (Al-Aqad, 2022)
The main point of this research is that the cost of buying and selling photocopies in the city of Sintang, West Kalimantan.. In this context, "cheap" means "affordable cost", "easy access", "useful", and "alternative options for people to meet needs". This study is a type of legal research that takes a qualitative approach and uses descriptive analysis. At the same time, the data collection procedure uses primary data (field research), such as observations, interviews, and documentation, so that researchers can process them. Books related to research topics and research results in the form of theses, theses, journals, and articles are examples of secondary data (library research). The analysis technique that the researchers use is the editing, classification, verification, and concluding stages. While in the data validity test stage, researchers use triangulation and member-check. The results show that; 1) This book sale and purchase transaction was motivated by a low price and market demand and availability of the photocopied book; 2) There is a form of difficulty in the process of finding original books and is also motivated by the limited economic conditions of consumers/buyers; 3) In the practice of buying and selling this book, there is a change of applicable law. The practice was originally considered haram but is now acceptable for individuals who have difficulty finding the original book; 4) In this study, two laws apply under two conditions, namely, buying photocopies for customers with sufficient and unimpeded funds is haram, while buying photocopies for consumers who have difficulty getting original books and with limited funds is legal. Keywords: Photocopy Book, MUI Fatwa, Intellectual Property Rights, Buying and Selling